Rancang Bangun Protoype Robot Navigasi Pemadam Api di Bandar Udara - Sunardi Sunardi; Julfansyah Margolang; Jhoni Hidayat; Iswandi Idris; Rizaldy Khair (Jurnal Sistem Komputer dan Informatika (JSON), 2020)
In aviation engineering, Aviation Safety must be an extreme concern for the government as a regulator / facilitator, each component of the Airport sub-system in conducting its operations must still prioritize flight safety and safety. In this case the supporting components and the utilization of AI technology are felt to be very necessary in order to complete the needs will Fulfill Flight Safety by utilizing robots as a medium. In general, robots can be defined as a mechanical device that is able to do human work or behave like humans. One of the human jobs that can be done by robots is fire fighting activities. In this study, researchers designed a Fire Extinguisher Robot to find and extinguish fire. The design of this robot uses an ultrasonic sensor HC-SR04 as a parameter for the robot's path when there are objects around and a fire sensor module as a detector for the presence of fire this robot uses MG995 servo that is useful as a controller hose from the water pump. The circuit in this robot has important components, the Arduino microcontroller functions as the brain of the robot and the L298P Motor Shield Driver functions as a DC motor drive module. If the robot detects a fire while walking, the robot will stop and extinguish the fire using water and candles are used as a fire simulation when a fire is happening.Â